Industry 4.0 readiness for the manufacturing sector in the Baltic Sea Region - Sara M. Bazaz (Estonian Academy Publishers, 2021)
This study provides data and analysis on the state of digitalization of the manufacturing industries in the Baltic Sea Region. The compiled matrix contains entities on seven fields of operation and lists ten service and technology areas mapped from Denmark, Estonia, Finland, Latvia, Lithuania and Poland. A comparison of the collected data estimates the level of digitalization as well as identifies potential strengths and weaknesses by region. The available support structure is analysed to find potentially suitable partners to improve the level of digitalization in the enterprises of a region. Furthermore, the strength areas of each country are compared to weak areas to develop a roadmap to improve the readiness for implementation and use of Industry 4.0 functionality and tools. Examples are provided on the generation of a BusinessÂtoÂBusiness (B2B) focused platform to improve the level of technologies and services in use, an example is also presented to identify and implement a use case based on an identified need.